Advances in comminution - Kawatra, S. K. (Society for Mining, Metallurgy, and Exploration, 2006)
There is a great deal of activity directed toward improving ore characterization to predict AG/SAG mill energy requirements, as well as developing improved models and instrumentation for optimization and control of comminution circuits. Instrumentation, modeling, and control functions in particular have benefited from rapidly advancing computer technology. These advances will keep energy waste to a minimum and will provide the increased energy efficiency needed to maintain ongoing success. The 36 chapters are based on the 2006 SME symposium. Topics and contributors were carefully selected to p.